Lingkungan Sekolah Sehat untuk Mencegah Stunting pada Anak SD - Ananda Putri Aliansy; Anna Maria Oktaviani; Suhernah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Stunting is a manifestation of chronic malnutrition that remains a major public health problem, particularly among school-aged children in developing countries, including Indonesia. In addition to inadequate nutritional intake, environmental factors such as poor sanitation, limited access to clean water, and unhealthy hygiene practices play a significant role in the occurrence of stunting. Schools, as a second environment after the family, have strategic potential to support stunting prevention through the implementation of a healthy school environment. This study aims to examine the role of a healthy school environment in preventing stunting among elementary school children. The research employed a quantitative approach with a quasi-experimental design, involving an intervention group and a control group. The study was conducted in two public elementary schools with a high prevalence of stunting. Data were collected through anthropometric measurements, questionnaires on Clean and Healthy Living Behavior (PHBS), and observations of school environmental health facilities. Data analysis used paired t-tests and independent t-tests to assess differences before and after the intervention. The findings indicate that the implementation of a healthy school environment program integrated with the School Health Unit (UKS) contributes positively to improving health behaviors and supporting optimal child growth. This study highlights the importance of cross-sector collaboration in strengthening sustainable school-based stunting prevention programs.